CONTENT OF POLYCYCLIC AROMATIC HYDROCARBON (PAHs) IN THE SEDIMENT OF THI NAI LAGOON (BINH DINH PROVINCE) - Kha, Pham Thi (Vietnam Journal of Marine Science and Technology, 2015)
Sediments in Thi Nai lagoon were collected and analysed to determine PAHs contents by gas chromatography with flame ionization detector (GC/FID). The analytic results showed that the content of total 8 PAHs ranged from 3.03 µg/kg dry weight to 113.77 µg/kg dry weight, with the average of 23.66 µg/kg dry weight. The concentration of total 8 PAHs was high in the top and middle of lagoon and low in the mouth of lagoon. However, the content of PAH congeners was lower than critical value in the National Technical Regulation on Sediment Quality (QCVN 43:2012/BTNMT). PAHs in Thi Nai lagoon were mainly with 4 - 5 rings, occupying 35.66 - 90.56% except for some stations (TN 14, TN8, TN17, TN - LT1). The initial result indicated that the source of PAHs in sediment of Thi Nai lagoon was from petrogenic.